Case Report: Failure of Therapeutic Coma in Rabies Encephalitis - Manesh, Abi (Am J Trop Med Hyg, 2018)
Rabies encephalitis is a fulminant, almost universally fatal infection involving the central nervous system. A unique treatment protocol, including anti-exicitotoxic therapy and induced coma was credited with the survival of a vaccinated teenager with bat rabies encephalitis in 2005. However, multiple efforts to replicate this expensive and intense protocol have not been successful. In this article, we report the failure of the protocol in Indian patients with canine-acquired rabies and elucidate the potential explanations for the failure of the protocol in our patients.